2014
DOI: 10.1144/sp406.5
|View full text |Cite
|
Sign up to set email alerts
|

Using mechanical models to investigate the controls on fracture geometry and distribution in chalk

Abstract: Chalk is an important reservoir rock. However, owing to its low permeability, fractures are key to producing hydrocarbons from chalk reservoirs. Fractures in chalk usually form one of three geometric patterns: localized fractures (commonly concentric rings) developed around tips, bends and splays in larger faults; regularly spaced regional fracture sets; and fracture corridors comprising narrow zones of closely spaced parallel fractures. Localized fracture patterns are likely to give only local permeability en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 56 publications
3
21
0
Order By: Relevance
“…Agosta et al 2010;Cilona et al 2012;Petrachinni et al 2013;Antonellini et al 2014). In this volume, Welch et al (2014) compare fault and fracture systems in two distinct chalk outcrops. Their approach offers a refreshing change in the pursuit of a more broadly applicable framework for fracture prediction.…”
Section: Selected Advancesmentioning
confidence: 98%
See 1 more Smart Citation
“…Agosta et al 2010;Cilona et al 2012;Petrachinni et al 2013;Antonellini et al 2014). In this volume, Welch et al (2014) compare fault and fracture systems in two distinct chalk outcrops. Their approach offers a refreshing change in the pursuit of a more broadly applicable framework for fracture prediction.…”
Section: Selected Advancesmentioning
confidence: 98%
“…These approaches can accelerate the exploration of key uncertainties. Welch et al (2014) explore the mechanical modelling of chalk. Recognizing the common patterns of faults and fractures that occur in different rock types and geological settings, this work explores the impacts of pre-existing structures and pore-fluid pressure on fracture development.…”
Section: Fundamental Controls On Fluid Flow In Carbonatesmentioning
confidence: 99%
“…Although absolute and even relative timing is notoriously hard to pin down (e.g., Peacock et al, ), fracture sets are commonly interpreted to have formed more‐or‐less contemporaneously over a short period of time (e.g., Caputo, ; Hancock, ). Yet some natural examples (Dunne & North, ) and model results (Bai et al, ; Nick et al, ; Olson & Pollard, ; Welch et al, ) imply that sets can form contemporaneously and/or over a long period of time (millions of years). Model results (e.g., Olson, ) show that complex patterns can arise from simple but protracted (millions of years) loading histories.…”
Section: The Challenge Of Natural Fractures In the Earthmentioning
confidence: 99%
“…examples (Dunne & North, 1990) and model results (Bai et al, 2002;Nick et al, 2011;Olson & Pollard, 1989;Welch et al, 2015) imply that sets can form contemporaneously and/or over a long period of time (millions of years). Model results (e.g., Olson, 2007) show that complex patterns can arise from simple but protracted (millions of years) loading histories.…”
Section: Reviews Of Geophysicsmentioning
confidence: 99%
“…In this paper, we investigate the impact of fluid pressure on fracture development. Previous work has suggested that the fracturing process in chalk is often governed by changes in fluid pressure, which also affect stress distributions (Welch et al, 2015). Before fracture initiation, the build-up of pore fluid pressure alters the local stress field by reducing effective stresses, thereby leaving the matrix more prone to tensile failure.…”
Section: Introductionmentioning
confidence: 99%